The Effectiveness of the Relaas Call in Settlement of Divorce Cases in the Religious Courts - Rosdalina Bukido; Fitriani Lundeto; Yasin Yasin (Al-'Adl, 2021)
Relaas call is one of the most important instruments in court proceedings. Without a call, the presence of the parties in the Court has no legal basis. Relaas Summons in the Civil Procedure Code is categorized as authentic deeds. Relaas did not convey to the parties in the litigation. The Respondent did not know about the trial schedule and the claim him, which resulted in the Respondent or Defendant losing the right to answer or defend himself against the plaintiffs' demands or the applicants. This study examines the Relaas summons' effectiveness through the Kelurahan in divorce cases at the Bitung Religious Court. Through field research with a qualitative descriptive approach using data mining techniques, observation, interviews, and documentation. The results prove that the Relaas concept in Islamic Law is contained in KHI Article 131, Articles 138 s.d. Article 140. Likewise, the Relaas image in positive Law is included in the Herzien Indlandsch Reglement or abbreviated as HIR and Rechtsreglement Voor de Buitengewesten, which are Civil Procedural Laws for areas outside Java and Madura. or abbreviated as RBg. The implementation of Relaas summons through the kelurahan was not effective in four cases, namely Case Number 55 / Pdt.G / 2018 / PA Bitg, Case Number 91 / Pdt.G / 2019 / PA Bitg, Case Number 0061 / Pdt.G / 2017 / PA Bitg and Case Number 0150 / Pdt.G / 2017 / PA. However, official and proper elements have subsequently been fulfilled.